Nas asas da identificação: uso de morfometria da asa em espécies de melipona - Silva-Neto, Carlos De Melo E.; Ribeiro, Anna Clara Chaves; Do Prado, Marco Antonio Pires Ferreira D.; Gonçalves, Bruno Bastos [UNESP]; Lima, Flaviana Gomes; Da Silva, Jaqueline Pinheiro [UNESP]; Nascimento, Abadia Dos Reis (My University, 2016)
The Melipona genus has the highest bee species richness of in Brazil, and the group needs taxonomic revision. Due to the difficulties in identifying bee groups, methods to facilitate and improve the identification of species are sought. This work aims to utilize the wing morphometry to differenciate between Melipona species. Five species of the genus were studied: Melipona quadrifasciata; M. rufiventris; M. mandacaia; M. marginata and M. fasciculata, and the morphometry of wing venules was used. Nine venules were measured in each collected indiconsideradas Flaviana Gomes Lima, Jaqueline Pinheiro da Silva and Abadia dos Reis Nascimento vidual, six of forewings and three hindwings. The morphometry of wings of different species of Melipona, leads to groups of species upon measuring the venules and analyzing them together. For Melipona quadrifasciata, which features four different populations, individuals of these populations were grouped within the same species, with no significant differences at the population level. Thus, it is concluded that the morphology of bee wings is efficient to distinguish between species of the genus Melipona.
On the wings of identification: Use of wings morphometry in melipona species